Higher education quality management: student quality management projects - Kurbonova, Nigora (Science and Education, 2023)
The importance of this article is dictated by the necessity to adopt the Europian standard of higher education including the module system into the frame of Uzbekistan university network. The author gives a brief review of the development of the quality concept and appoaches, which have been made to integrate it into the higher education management. The article draws the new scheme of the individual work of student management seen as part of the general management process.